The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00125-008-1182-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic factors and pre-eclampsia in type 1 diabetic women

Abstract: Aims/hypothesis Elevated anti-angiogenic factors such as soluble fms-like tyrosine kinase 1 (sFlt1), a soluble form of vascular endothelial growth factor receptor, and endoglin, a co-receptor for TGFβ1, confer high risk of pre-eclampsia in healthy pregnant women. In this multicentre prospective study, we determined levels of these and related factors in pregnant women with type 1 diabetes, a condition associated with a fourfold increase in pre-eclampsia. Methods Maternal serum sFlt1, endoglin, placental growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 31 publications
(48 reference statements)
5
79
0
3
Order By: Relevance
“…Throughout pregnancy, ANP levels were 34% higher in these women (41). As in pre-eclampsia in nondiabetic women, pre-eclampsia in women with type 1 diabetes is also associated with elevated levels of antiangiogenetic factors in the third trimester (27). However, the function of placenta in the early stage of pregnancy judged by the level of activin A and inhibin A is often well preserved in diabetic women developing pre-eclampsia (42).…”
Section: Pre-eclampsia and Vasoactive Markersmentioning
confidence: 90%
See 2 more Smart Citations
“…Throughout pregnancy, ANP levels were 34% higher in these women (41). As in pre-eclampsia in nondiabetic women, pre-eclampsia in women with type 1 diabetes is also associated with elevated levels of antiangiogenetic factors in the third trimester (27). However, the function of placenta in the early stage of pregnancy judged by the level of activin A and inhibin A is often well preserved in diabetic women developing pre-eclampsia (42).…”
Section: Pre-eclampsia and Vasoactive Markersmentioning
confidence: 90%
“…However, supplementation with vitamins C and E in a randomized study including 762 women with type 1 diabetes did not reduce the risk of pre-eclampsia (30). As in pre-eclampsia in women without diabetes, pre-eclampsia in women with type 1 diabetes is also associated with elevated levels of antiangiogenetic factors in the third trimester (27).…”
Section: Pathophysiology Of Pre-eclampsia and Hypertension In Diabetimentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, these factors have also been implicated in the pathogenesis of the vascular complications of diabetes (12,13), suggesting that common mechanisms might underlie PE and diabetic vascular complications. Our own studies show a general elevation of endoglin among T1DM women in later pregnancy (ϳ30 wk, but before PE onset) (14). Because endoglin is one of only two antiangiogenic factors that, together, are thought to constitute a prerequisite for PE (8), this could explain the high prevalence of PE in diabetes.…”
mentioning
confidence: 96%
“…The study was conducted according to the principles of the Declaration of Helsinki, and all study participants provided written informed consent at the study centers (Australia, Norway, and United States) as previously reported (14). In the first trimester of pregnancy, 151 women with established T1DM and 24 healthy nondiabetic women were recruited.…”
Section: Study Design and Participantsmentioning
confidence: 99%